Birds of Australia : A Photographic Guide - Campbell, Iain, 1969- (Book collections on Project MUSE., 2015)
This guide covers 714 species of resident Australian birds and regularly occurring migrants. It describes key identification features such as size, plumage, distribution, behavior, and voice, as well as habitat descriptions.